Indonesia's International Cooperation in Promoting the Clean Energy Transition within the Framework of the Paris Agreement - Sipa Nuraeni; Maulana Rifai (al-Afkar, Journal For Islamic Studies, 2026)
Climate change has prompted Indonesia to transition to clean energy as part of its global commitment under the Paris Agreement. One important effort in supporting this transition is through international cooperation, particularly to overcome limitations in funding, technology, and national capacity. This study aims to analyze the role of international cooperation in promoting clean energy transition in Indonesia and identify the challenges of its implementation. The study uses a descriptive qualitative approach with a literature review and document analysis of national policies, such as Nationally Determined Contributions (NDCs), as well as reports from international institutions and relevant academic literature. The results show that international cooperation contributes significantly through the provision of climate finance, technology transfer, and capacity building in renewable energy development. However, its effectiveness still faces regulatory and bureaucratic obstacles, funding challenges, as well as social and institutional factors. This study concludes that strengthening national governance and synergizing domestic actors are key to optimizing international cooperation in supporting Indonesia's clean energy transition.